Successful Treatment of Osteitis Fibrosa Cystica from Primary Hyperparathyroidism - Anthony M. Maina; Harry Kraus (Case Reports in Orthopedics)
Osteitis Fibrosa Cystica (OFC) is defined as the classic skeletal manifestation of advanced primary hyperparathyroidism. With the increased detection by means of routine calcium screening, the clinical profile of primary hyperparathyroidism in Western countries has shifted from symptomatic disease to one with subtle or no specific symptoms (“asymptomatic” primary hyperparathyroidism). The authors describe a classical feature of advanced primary hyperparathyroidism due to a parathyroid adenoma and its successful treatment.